The impact of 'load-shedding' within the Nelson Mandela Bay restaurant industry - Botha, Tamsyn (The IIE, 2019)
Eskom’s supply of electricity serves as an imperative input for many business operations in South Africa, presenting the problem analysed in this study. Since the implementation of ‘load-shedding’ in 2008, many small businesses have struggled to reach their maximum productivity as research states they do not possess the resources to mitigate the effects of ‘load-shedding’, hindering their ability to survive. South Africa’s economic growth and development is highly reliant on the productivity and survival of small enterprises. The primary objective of this study is to evaluate the impact ‘load-shedding’ has on the productivity of restaurants, within Nelson Mandela Bay. This study provides a quantitative approach towards, whether there is an impact of ‘load-shedding’ amongst restaurants, how their inputs and outputs are impacted and what mitigation techniques they have implemented. Questionnaires were developed, administrated, collected and evaluated by the researcher, to a sample of 20 respondents. This data produced significant findings of 73% of respondents identifying ‘load-shedding’ as a major concern and contrary to small enterprises lacking in resources, 93% of respondents invested into a secondary energy source to alleviate ‘load-shedding’ impacts. The study’s key contribution aimed to understand the negative impact of ‘load-shedding and the most popular mitigation technique.
Keywords: load-shedding; small businesses; Nelson Mandela Bay restaurants; impact on productivity; mitigation technique